1986
DOI: 10.1055/s-0038-1661637
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand Factor in Cultured Human Vascular Endothelial Cells from Adult and Umbilical Cord Arteries and Veins

Abstract: SummaryEndothelial cells were cultured from various human arteries and veins, obtained from adult individuals and from umbilical cords. We compared the storage and secretion of von Willebrand factor by endothelial cells from umbilical veins with that of endothelial cells cultured from a number of adult vessels, including aorta, arteria iliaca, vena saphena magna and vena cava. There were no differences in the way the cultured endothelial cells handled the von Willebrand factor they synthesized. Endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Although there were reports on cellular behavior dependence on the adsorbed fibronectin rather than on the underlying substrata, for example, Lewandowska et al reported that different surfaces bind similar amounts of fibronectin and cell attachment to these surfaces is similar [31], others found that the amount of cell-binding activity was the same for hydrophilic tissue cultures on polystyrene (TCPs) or hydrophobic polystyrene (BPS) at higher densities of adsorbed fibronectin [32][33][34]. In our study, both XPS results and ELISA assay demonstrated that the highest fibronectin was adsorbed on Fn-PHBHHx while its cell affinity was not the highest among all test films.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were reports on cellular behavior dependence on the adsorbed fibronectin rather than on the underlying substrata, for example, Lewandowska et al reported that different surfaces bind similar amounts of fibronectin and cell attachment to these surfaces is similar [31], others found that the amount of cell-binding activity was the same for hydrophilic tissue cultures on polystyrene (TCPs) or hydrophobic polystyrene (BPS) at higher densities of adsorbed fibronectin [32][33][34]. In our study, both XPS results and ELISA assay demonstrated that the highest fibronectin was adsorbed on Fn-PHBHHx while its cell affinity was not the highest among all test films.…”
Section: Discussionmentioning
confidence: 99%
“…28 For example, differences have been found for the synthesis of prostacyclin, 29 vWF expression, 30 fibrinolytic activity, 31 • 3Z synthesis of platelet activating factor, 33 and the sensitivity for hormones. 34 For this reason, we studied endothelial cells isolated from human large vessels, from umbilical vein, and from microcirculation and compared them with SMC and Fb.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs) were isolated from umbilical veins according to the method of Jaffe et al 32 and modified by Van Wachem et al 33 In short, the umbilical vein was rinsed with PBS and incubated for 20 min at 37°C in 0.05% trypsin-0.02% EDTA solution in PBS. CMS was added to inactivate trypsin, and after exchange of the medium by fresh medium, cells were plated in fibronectincoated TCPS flasks and grown until the third passage.…”
Section: Isolation Of Endothelial Cellsmentioning
confidence: 99%